Ethics of Care: A Perspective on Nutrition in Advanced Cancer - Monica de Oliveira Benarroz; Rocio Fernandez Santos Viniegra; Edna Corrêa Moreira; Rodrigo Siqueira-Batista (Revista Iberoamericana de Bioética, 2025)
Nutrition-related problems are common in advanced cancer but are not always properly identified and treated. Food is highly symbolic, establishing a strong connection to life and well-being. The inability to eat and drink is associated with disease progression and death. Nutritional care is the most effective way to address these issues through responsible, conscientious, and compassionate support. In both the ethics of care and palliative care, the relationship and commitment to vulnerable individuals are integral to daily health practices. Through the lens of the ethics of care, we argue that nutritional care provided by dietitians is crucial in palliative care to address nutrition-related issues, resolve moral conflicts and dilemmas, and prevent an increase in vulnerabilities and violations of the rights of patients and families.